Progrès dans l’impasse : critiques de Celal Nuri et Filibeli Ahmed Hilmi vis-à-vis des puissances européennes (1910-1914) - Ömer Köksal (European Journal of Turkish Studies)
This study examines the existential impasse that two Ottoman reformist intellectuals experienced, Filibeli Aḥmed Ḥilmī (1863-1914) and Celāl Nūrī (1882-1938), both produced similar works in the years preceding The First World War (1914-1918). As a methodology, this work adopts the history of concepts (Begriffsgeschichte) developed especially by Reinhart Koselleck. In so doing, it enables to open new horizons in the Ottoman studies that hardly took into consideration the temporal questions inscribed in the concepts, except for a diachrony between European and Ottoman intellectual productions. Therefore, it aims to re-inscribe the concepts in their own space of experience and horizon of expectation. Establishing the relation between meaning and use of the concepts, it avoids assigning pre-established intentions to the intellectuals in question. For this, it intends to dissect semantic structures of the related concepts used by these two intellectuals, namely progress (teraḳḳī), decline (inḥiṭāṭ, tedennīyāt), right (ḥaḳḳ) and total annihilation (helāk), while paying particular attention to the semantical relations between them. Writing in a period when their hopes for the survival of the Ottoman Empire are quickly dashed, faced with an increasingly inauspicious future, Ḥilmī and Nūrī also consider themselves as inheritors of a long past of decline. Thus, aporia reigns where there is no way out either towards the past or the future.